O uso de tecnologias como ferramenta de apoio às aulas de geometria - Kitaoka, Alessandra de Carvalho (2013)
This project's main goal is propose the application of a Teaching Sequence about how finding the notable points of a triangle, in particular, the circumcenter. Introducing in the sequence geometric objects primaries of Euclidean geometry with the axioms and the theorems necessary to construct the circumcenter. The geometric objects will be built through educational software Geogebra. The teaching of geometry, often present to the end of the textbook, is faced with the difficulty of the students to manipulate instruments as ruler, protractor and compass. On the other hand, the fascination of students by computers facilitates the use of geometric softwares. The sum of these factors, have inspired this project. Based on the methodology of the didactic engineering I intend to show the construction steps of mathematical knowing from the student's research experimenting, visualizing, conjecturing, generalizing even demonstrating the mathematical basement in this context.